Prevalence of selected enteropathogenic bacteria in Hungarian finishing pigs - Biksi, I; Lorincz, Márta; Molnár, Beáta; Kecskés, T; Takács, N; Mirt, Darja; Cizek, A; Pejsak, Z; Martineau, G P; Sevin, J L; Szenci, O (Acta veterinaria Hungarica (Budapest. 1983), 2007)
The aim of this study was to obtain prevalence estimates about the most important enteropathogenic bacteria: Lawsonia intracellularis, Brachyspira hyodysenteriae, Brachyspira pilosicoli, Salmonella enterica and Clostridium perfringens A and C in Hungarian farrow-to-finish pig herds. A total of 31 herds were selected, from where six pooled faecal samples, each containing three individual rectal faecal samples were collected from fattening pigs of 5-6 months of age. All 186 samples were examined by polymerase chain reaction (PCR) for the presence of the pathogens mentioned above. Lawsonia intracellularis was found in 29 herds (93.55%) and in 108 samples (58.06%); B. hyodysenteriae in 14 herds (45.16%) and in 23 samples (12.37%); B. pilosicoli in 19 herds (61.29%) and in 53 samples (28.49%); S. enterica in 17 herds (54.83%) and in 40 samples (21.50%). We detected the presence of C. perfringens A in 19 herds (61.29%) and in 46 samples (24.73%), while C. perfringens C was found in 8 herds (25.81%) and in 11 samples (5.91%). All examined herds were infected with one or more of these agents. Herds with diarrhoea in the mid- to late finishing phase had almost 10 times higher prevalence of B. hyodysenteriae than herds without such a history.